A NIR turn-on fluorescent probe for specific recognition of cysteine and its application in cells and zebrafish. (December 2022) - Zhang, Meng; Zhang, Yongbin; Huo, Fangjun; Chao, Jianbin; Shuang, Shaomin
Abstract: A new turn-on fluorescent probe (DC-O-SBD ) for cysteine (Cys) with a large Stokes shift was synthesized. Free DC-O-SBD had almost no fluorescence. After reacting with Cys, it released near-infrared (NIR) fluorescence at 655 nm. DC-O-SBD can respond to Cys quickly and had high specificity for Cys. Moreover, DC-O-SBD had a low detection limit (0.16 μM) and a large Stokes shift (155 nm). In addition, DC-O-SBD can efficiently detect Cys in HeLa cells and zebrafish. Graphical abstract: Image 1 Highlights: A new fluorescent probe was synthesized from 4-diethylaminosalicylaldehyde and 2-(3, 3, 5-trimethylcyclohexylidene)malononitrile with SBD-Cl as a recognition group. A NIR turn-on fluorescent probe for specific recognition of cysteine with a large Stokes shift (155 nm). The probe had a low detection limit of cysteine was 0.16 μM. The probe has been successfully applied to the detection of cysteine in HeLa cells and zebrafish.